2017
DOI: 10.1002/fsn3.525
|View full text |Cite
|
Sign up to set email alerts
|

Malting and fermentation effects on antinutritional components and functional characteristics of sorghum flour

Abstract: The research was aimed to observe the effect of malting and fermentation on antinutritional component and functional characteristics of sorghum flour. For whole sorghum flour, cleaned sorghum grain was milled to pass through 40 mesh sieve. For malting, cleaned sorghum grain was steeped in 0.2% calcium hydroxide solution for 24 hr and then germinated for 48 hr at 90% RH and 27 ± 2°C. Sprout was removed, dried in hot air oven at 50 ± 2°C for 24 hr and milled to pass through 40 mesh sieve. For fermented sorghum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 44 publications
4
39
0
1
Order By: Relevance
“…The density of Xveola‐45 , Muktinath , Xveola‐38 , NB‐1003/37‐1038 , and Bonus significantly decreased ( p < .05) after malting, while the viscosity of all the genotypes decreased significantly ( p < .05) after malting. Ojha et al (2018) reported a decrease in bulk density and viscosity of sorghum after malting. The decrease in bulk density and viscosity may be due to the breakdown of starch and other high molecular components due to enzymatic activity, and change in surface properties (Chinma et al, 2017; Oti & Akobundu, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The density of Xveola‐45 , Muktinath , Xveola‐38 , NB‐1003/37‐1038 , and Bonus significantly decreased ( p < .05) after malting, while the viscosity of all the genotypes decreased significantly ( p < .05) after malting. Ojha et al (2018) reported a decrease in bulk density and viscosity of sorghum after malting. The decrease in bulk density and viscosity may be due to the breakdown of starch and other high molecular components due to enzymatic activity, and change in surface properties (Chinma et al, 2017; Oti & Akobundu, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, it is categorized as having low nutritional values. Fermentation of sorghum diminished oxalate, phytate, and tannins by 49.1%, 40%, and 16.12%, respectively [70].…”
Section: Fermentationmentioning
confidence: 97%
“…It has been reported that it is an essential and principle source of protein, energy, and minerals in diets for both animals and humankind in tropical and subtropical areas [4]. Previous studies have shown that sorghum contains anti-nutritional factors like tannin, phytic acid, cyanogenicglucoside, oxalate, and trypsin inhibitor [69,70]. For these reasons, it is categorized as having low nutritional values.…”
Section: Fermentationmentioning
confidence: 99%
“…On the other hand, prolonged soaking and fermentation can help reduce the content of these phytochemicals through leaching (Ogbonna et al, 2012). Microbial activity during fermentation process reduces tannin content as does the activity of the enzyme tannin acyl hydrolase (Ojha et al, 2018). Owing to the reduction in the tannin and phytic acid content in malted cereals, minerals are made more bioavailable, thereby increasing the nutritional value of the food (Ogbonna et al, 2012;Oghbaei & Prakash, 2016).…”
Section: Phytochemicalsmentioning
confidence: 99%